Palm oil plantation waste handling by smallholder and the correlation with the land fire - H. Herdiansyah; E. Frimawaty (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: From August to October 2019, several provinces in Sumatra and Kalimantan had faced severe forest fires, causing thousands of citizens to suffer respiratory disorders. This study aims to assess waste handling in palm oil plantation manage by smallholders and the correlation palm oil plantation waste handling with the fireland in Sumatera, especially on Jambi province. METHODS: Primary data collection was conducted in September 2019, and a purposive random sampling method was used to select respondents. Primary data collection was applied for four hundred smallholders in five districts in Jambi using a mixed method. FINDINGS: Out of 400 correspondents that handle their waste, 50% of respondents handle the residues by stacking the waste on their field, 25% of correspondents stack the waste between trees, 17.25% of correspondents stack the waste on piles, 5% of them bury the posts, and 2.75% incinerate the waste. The average distance from home to the field for 200 correspondents is 8.825 kilometres, and they have the highest harvest quantity with a mean of 1.0940 tons. Most of them are common smallholders and self-subsistent smallholders. The 298 correspondents join a farming association. About 50% of smallholders in Jambi handle the residues by stacking the wastes on their field instead of incinerating the waste. CONCLUSION: Out of the overall samples collected in this study, only 2.75% smallholders in Jambi incinerate their residues. Hence, the fire breakouts happened on several provinces in Sumatera and Kalimantan in late 2019 did not happen due to crude palm oil waste-handling activities.